Strategi Pemasaran Layanan Jasa Tabungan Pada Masa Pandemi: Studi Kasus PT Bank Negara Indonesia KCP. Poso - Vera Roncalangi; Abdi Sakti Walenta; Silvany Annatje Taariwuan (Interdisciplinary Journal (IDe), 2023)
This study aims to find out about the marketing strategy of savings services during the pandemic at PT. Bank Negara Indonesia (BNI) KCP Poso. This research uses a qualitative approach that focuses research data on key information related to marketing strategies for savings services during the pandemic. Marketing Strategy Concept at PT. Bank Negara Indonesia (BNI) KCP Poso is centered on products, prices, promotions and company locations. Based on the results of the analysis, there have been several problems or obstacles that occurred during the pandemic. However, PT Bank Negara Indonesia (BNI) Kcp Poso has its own strategy to maintain and increase the service and number of savings customers at BNI Poso. To improve the marketing strategy of savings services during the pandemic, PT Bank Negara Indonesia (BNI) KCP Poso uses several components in implementing marketing strategies, namely 4P or usually consisting of products, prices, places and promotions. Of all the efforts that have been made, the most influential strategy during the pandemic is to utilize banking digitalization and social media, improving features that can make it easier for customers to make transactions without having to go to BNI Poso. Thus, the strategy has run as desired and the number of customers has no effect on the pandemic so that every year customers continue to increase.